2018
DOI: 10.1029/2018jf004703
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic Evolution of a Gravel‐Bed River Under Sediment‐Starved Versus Sediment‐Rich Conditions: River Response to the World's Largest Dam Removal

Abstract: Understanding river response to sediment pulses is a fundamental problem in geomorphic process studies, with myriad implications for river management. However, because large sediment pulses are rare and usually unanticipated, they are seldom studied at field scale. We examine fluvial response to a massive (~20 Mt) sediment pulse released by the largest dam removal globally, on the Elwha River, Washington, United States, in an 11‐year before‐after/control‐impact study of channel morphology and grain size. We te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 147 publications
(366 reference statements)
6
101
0
Order By: Relevance
“…East et al . () did find that reductions in upstream sediment supply had little effect on channel stability in the downstreammost reaches of the Elwha River (downstream of Elwha Dam) but suggest that sediment recruitment from large bluffs in that area may constitute a significant portion of the sediment budget. While we conclude that dam emplacement in systems similar to the Elwha River results in increased bed stability and a reduction in channel width, our model results imply that channel‐floodplain exchange does still occur in sediment‐starved systems, albeit less frequently and at a much lower magnitude.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…East et al . () did find that reductions in upstream sediment supply had little effect on channel stability in the downstreammost reaches of the Elwha River (downstream of Elwha Dam) but suggest that sediment recruitment from large bluffs in that area may constitute a significant portion of the sediment budget. While we conclude that dam emplacement in systems similar to the Elwha River results in increased bed stability and a reduction in channel width, our model results imply that channel‐floodplain exchange does still occur in sediment‐starved systems, albeit less frequently and at a much lower magnitude.…”
Section: Discussionmentioning
confidence: 94%
“…() both found that the Middle Elwha was stable in the decade prior to dam removal; Pohl () concludes that the reach had low bed mobility compared to reaches upstream of the dam, and East et al . () did not observe channel width change in the reach following a 50‐year flood, but admit that data resolution is coarse in that area. East et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have learned much by analyzing fluvial responses to past events. Studies have shown that geomorphic responses to fluvial disturbances (1) relax over varying timescales but can persist for years to decades, even centuries; (2) can be both acute and gradual; (3) are influenced by many factors including hillslope‐channel coupling, physical linkages among channel reaches, and hydrological regimes; (4) can follow many trajectories; (5) are intricately intertwined with ecological recovery; and (6) that systems may not return to predisturbance states (e.g., Bellmore et al, ; Cluer & Thorne, ; East et al, ; Foley et al, ; Gellis et al, ; Gran et al, , ; James, ; James & Lecce, ; Kasai, ; Kasai et al, ; Major et al, ; Moody & Meade, , ; Pierson & Major, ; Schumm, ; Swanson & Major, ). But we can further exploit records of physical responses to profound fluvial disturbances to gain richer geomorphic insights.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of geomorphic responses to fluvial perturbation have been approached in many ways. But aside from small‐scale analog models (e.g., Baynes et al, ; Lisle et al, ; Schumm, ; Schumm et al, ) and numerical models (e.g., Limaye & Lamb, ; Malatesta et al, ), few studies actually document long‐term channel evolution following disturbance of a dynamically stable river (e.g., East et al, ; Gellis et al, ; Gran et al, ; Kasai, ; Kasai et al, ; Lauer et al, ; Leopold, ; Meyer et al, , ; Moody et al, ; Moody & Meade, , ; Tunnicliffe et al, ), and even fewer record spatiotemporal variations of the relative efficacies of vertical versus lateral adjustments in the fluvial system (e.g., East et al, ; Meyer & Martinson, ; Moody & Meade, ). This is not surprising; few rivers exist where substantial (kilometers‐long) reaches are effectively reset and reestablished over human (decadal) timescales or where it has been possible to sustain multiyear, let alone multidecadal, monitoring.…”
Section: Introductionmentioning
confidence: 99%